THE INFLUENCE OF COLLECTION OF PARKING TAX, STREET LIGHTING TAX, ENTERTAINMENT TAX AND HOTEL TAX ON MEDAN CITY REGIONAL ORIGINAL INCOME - Mesrawati -; Dina Pasaribu; Dorisna Simamora; Hariyanti Purba; Junita Putri Rajana Harahap (Jurnal Ipteks Terapan, 2023)
The goal of this study was to gather data on how municipal revenue in the city of Medan was affected by parking fees, fees for street lighting, fees for lodging, and fees for entertainment. The dependent variable in this study is the local revenue of the city of Medan, and the independent variables employed in it are parking taxes, street lighting charges, hotel taxes, and entertainment taxes. The population used in this analysis is represented by a report on budget realization for the years 2018–2021. The study sample was determined using historical data as well as information from the yearly Regional Original Revenue Budget Realization Report. Multiple Regression Analysis, Descriptive Statistical Analysis, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test), t test, F test, and Coefficient of Determination were used to analyze the data using SPSS version 20. The findings of this study show that local revenue is positively impacted by parking taxes, street lighting taxes, hotel taxes, and entertainment taxes.